SISTEM PENGETAHUAN TRADISIONAL DALAM MENANGKAP IKAN PADA NELAYAN PANCING DAN JARING DI NAGARI SURANTIH KABUPATEN PESISIR SELATAN SUMATERA BARAT - AJISMAN AJISMAN; ROIS LEONARD ARIOS (Pangadereng : Jurnal Hasil Penelitian Ilmu Sosial dan Humaniora, 2021)
This study aims to reveal the traditional knowledge system of fishing rods and net fishermen in Nagari Surantih, Pesisir Selatan Regency, West Sumatra Province. This departs from the idea that traditional fishing communities rely on knowledge of natural signs in their fishing activities. This knowledge is a process of social action to achieve goals. The research was conducted with a qualitative approach with data collection techniques through interviews, observations, and literature studies. The analysis was carried out through domain and taxonomy analysis. The results showed that traditional fishermen in Nagari Surantih were divided into two groups, namely fishing rods and net fishermen. However, all fishermen agreed that being able to become fishermen must understand the signs of nature in order to be safe while fishing and get a good catch. Natural signs that are important to understand are the position of the stars and moon at night, ferocity, moon sickness, rain that is considered unnatural, birds, sunsets, water currents, and instincts. This whole system of knowledge was obtained from their respective parents